2020
DOI: 10.5114/pjr.2020.97008
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transthoracic needle biopsy for pulmonary nodules: a retrospective study of a comparison between C-arm cone-beam computed tomography and conventional computed tomography guidance

Abstract: Purpose: To evaluate the safety and diagnostic performance of pulmonary nodule biopsies using cone-beam computed tomography (CBCT) guidance compared with conventional CT (CCT) guidance. Material and methods: Patients who had pulmonary nodules and underwent a transthoracic needle biopsy at the interventional unit from January 1, 2013 to June 30, 2018 were enrolled. CBCT with XperGuide software was used to biopsy 100 nodules, and CCT guidance was used to biopsy 266 nodules. The two techniques were compared in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although CBCT is inferior to conventional CT in terms of imaging range and density resolution, in most cases it is sufficient to meet the clinical needs of guiding puncture and confirming the positional relationship of lesions and needle tips. Previous studies have showed that CBCT‐guided PTNB has a noninferior diagnostic accuracy for malignancy compared to conventional CT (94.9%–96.0% vs. 89.9%–95.3%) 69–71 . In comparison, conventional CT requires more room for the gantry frame and has a smaller inner space, which makes operations more challenging.…”
Section: Clinical Application Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CBCT is inferior to conventional CT in terms of imaging range and density resolution, in most cases it is sufficient to meet the clinical needs of guiding puncture and confirming the positional relationship of lesions and needle tips. Previous studies have showed that CBCT‐guided PTNB has a noninferior diagnostic accuracy for malignancy compared to conventional CT (94.9%–96.0% vs. 89.9%–95.3%) 69–71 . In comparison, conventional CT requires more room for the gantry frame and has a smaller inner space, which makes operations more challenging.…”
Section: Clinical Application Recommendationsmentioning
confidence: 99%
“…Previous studies have showed that CBCT‐guided PTNB has a noninferior diagnostic accuracy for malignancy compared to conventional CT (94.9%–96.0% vs. 89.9%–95.3%). 69 , 70 , 71 In comparison, conventional CT requires more room for the gantry frame and has a smaller inner space, which makes operations more challenging. Additionally, there is a higher chance of instrument displacement when patients are frequently moved in and out of the CT gantry for scanning and puncturing.…”
Section: Clinical Application Recommendationsmentioning
confidence: 99%